The effect of net metering methods on prosumer energy settlements. (September 2021) - Ziras, Charalampos; Calearo, Lisa; Marinelli, Mattia
Abstract: Net metering is a well-known mechanism, where only energy exchanges of prosumers with the grid are accounted for in settlements. What is less known is the subtleness of the metering practices of energy suppliers behind the reported energy values. This paper discusses the implications of applying different net metering methods on a prosumer's energy exchanges with the grid, and subsequently the effect on costs and self-consumption. The methods differ on whether netting is based on each individual phase (or on the overall energy flow) and the netting interval used for settlement. Besides describing and illustrating those differences, real data from a Danish household is used to quantify their impact. Results show that self-consumption increases from 38% to 53%, when moving from instantaneous per phase netting to hourly summation netting. The corresponding annual energy imports decrease from 1459 kWh to 1087 kWh. The economic implications of applying different netting methods are quantified and discussed, and we show that annual savings of at least €50 can be achieved by simply switching to a summation smart meter.